Neurofilament Light Chain serum levels after Hypoxia-Ischemia in a newborn piglet model - Kyng, Kasper Jacobsen; Wellmann, Sven; Lehnerer, Verena; Hansen, Lærke Hjøllund; Kuhle, Jens; Henriksen, Tine Brink (Frontiers in Pediatrics, 2023)
Aim: Neurofilament light Chain (NfL) is a promising brain injury biomarker which may assist diagnosis and prognostication in hypoxic-ischemic encephalopathy (HIE). The aim of this study was to investigate serum NfL levels after hypoxia-ischemia (HI) in a newborn piglet model. Second, to characterize the influence of sex, weight, and treatment with remote ischemic postconditioning (RIPC) on NfL and the correlation between NfL, brain imaging and histologic brain injury. Methods: We used serum from 48 newborn piglets of both sexes subjected to 45 minutes of global HI, and 4 sham piglets. Blood was collected pre-HI, 2h post-HI and 72h post-HI. NfL was measured by single-molecule array (SimoaTM). We analysed the temporal profile of NfL after HI, and correlations between NfL, magnetic resonance spectroscopy brain Lac/NAA ratios and histologic brain injury 72 hours after HI. Results: Median (IQR) NfL levels were: pre-HI: 66pg/ml (45-87), 2h post-HI: 105 pg/ml (77-140), and 72h post-HI: 380 pg/ml (202-552). The increase in NfL after HI was statistically significant (p < 0.0001, mixed-effects ANOVA). Median NfL levels in sham animals were 41.4 pg/ml at baseline and 92.4 pg/ml at 72h (p = 0.11, paired t-test). Neither sex, nor treatment with RIPC influenced NfL levels. Weight had a small, not biologically important, influence. NfL levels at 72 hours were moderately correlated with histologic brain injury and brain Lac/NAA ratios. NfL 72h post-HI > 330 pg/ml had a sensitivity of 89% (95% CI 57-99%) and a specificity of 52% (95% CI 34-69%) for predicting basal ganglia Lac/NAA ratio in the highest quartile. NfL 72h post-HI > 445 pg/ml had a sensitivity of 90% (95% CI 60-99%) and a specificity of 74% (95% CI 58-86%) for predicting cortical brain histopathology injury in the highest quartile. Conclusion: NfL increased after HI, with the largest values at 72h post-HI. Early NfL was sensitive but not very specific, whereas NfL at 72h was both highly sensitive and specific for exposure to moderate-severe HI in this model of HI-induced brain injury. This was supported by a moderate correlation of NfL at 72h with brain Lac/NAA ratio and histopathology.